Cycling exposure and infrastructural correlates in a Flemish adolescent population. (March 2020) - Vanparijs, J.; Van Cauwenberg, J.; Int Panis, L.; Van Hecke, E.; Gillis, D.; Gautama, S.; Meeusen, R.; de Geus, B.
Abstract: Introduction: Infrastructure adjusted to cyclists can be used as a tool to reduce cycling crashes and injuries. To increase cycling frequency and safety, a population's cycling exposure to different infrastructure needs to be known. Since cycling behavior of adolescents cannot be compared to adults, the objective of this study is to describe the cycling exposure and the characteristics of routes used by adolescents for bicycle commuting. Methods: We used an online travel diary to collect bicycle route information and an exposure matrix to collect cycling frequency data. Data were collected in Flanders (Belgium) from an adolescent population (15–18 years). Results: From the 1345 participating adolescents, 47% used their bicycle at least once a week. Infrastructural correlates were based on 467, 000 km of cycled roads with a mean trip distance of 5.7 ± 4.5 km; 91% of cycling exposure is on infrastructure with speed limits of 50 km/h or more and 32.7% on dedicated cycle lanes. Lower motorized traffic density was related to higher odds of daily bicycle commuting. Higher traffic densities or speed limits were related to lower odds of daily bicycle commuting, but this relationship disappeared after adjusting for presence of a dedicated cycle lane. Conclusions: Many adolescents who commute by bicycle cycle along streets with high speed limits and no dedicated cycle lanes probably because of the low motorized traffic densities on these roads. Adolescents should avoid roads without dedicated cycling infrastructure and high speed limits since these roads have been identified as high risk. The results are region specific and therefore this study should be replicated in other contexts. Highlights: We analyzed the cycling exposure and the characteristics of routes used by adolescents for bicycle commuting. In Flanders, 47% of the adolescents commutes by bicycle with an average trip distance of 5.7 km. 91% of adolescents cycling exposure is on road infrastructure with speed limits of 50 km/h or more. Lower traffic density increases the odds of commuter cycling irrespective of the presence of dedicated cycle lanes.